Iris yellow spot virus in Colorado onions: a survey of its spatial distribution and techniques to manage the pest - Fichtner, Scott M., author; Schwartz, Howard F., advisor; Hill, Joe, advisor (Colorado State University. Libraries, 2007)
The Iris yellow spot virus (IYSV) is a new, and at times devastating pathogen of alliums throughout the U.S. as well as many other countries. Since its discovery in Colorado in 2001, IYSV has been identified in nearly all of the major onion producing regions within the state. The severity of this virus disease appears to fluctuate from one year to the next but incidence continues to increase with newly infested fields identified each year. With the number of outbreaks on the rise and the inadequacy of current control strategies, new management techniques as well as novel chemistry pesticides have become a major focus for the management of this virus disease and its thrips vector. Our trials demonstrated the use of reflective materials such as straw or silver reflective mulch can result in a reduction in thrips populations by as much as 69% on onions and a reduction of nearly 9% in IYSV disease incidence. Additionally, Entrust (Spinosad) and Aza-Direct (Neem extract) were found to work as well as or better than conventional materials such as Warrior (Pyrethroid) and Lannate (Carbamate). To better understand the epidemiology of the IYSV pathogen, we also conducted an extensive survey at several locations along the Colorado Front Range and Western Slope. In our surveys, we collected information including thrips populations and incidence of IYSV using 0.2 ha grids developed using mapping software (MapInfo) creating several randomly chosen plots in each field. With data collected on several sampling dates, we attempted to identify a spatial correlation of within field spread of the virus during the growing season. The levels of positive spatial autocorrelation from our survey locations were minimal, this leads us to believe that secondary outbreaks of the disease are occurring in a random fashion across the field.
Keywords: iris yellow spot virus; onions; pest management; plant pathology